Effect of gastro-oesophageal reflux on upper oesophageal sphincter motility in children. Issue 7 (July 1993) - Willing, J; Davidson, G P; Dent, J; Cook, I
Abstract : Motor events of the upper oesophageal sphincter associated with gastro-oesophageal reflux were evaluated in 53 symptomatic children (median age 13 months) who were studied recumbent and unsedated. Children were divided into four groups according to symptoms, and then into two groups according to the presence or absence of neurological deficit. No grouping had basal upper oesophageal sphincter pressure that differed significantly from any other. Oesophageal distention due to gastro-oesophageal reflux, which was recognisable as oesophageal common cavity episodes, was associated with augmentation of mean basal upper oesophageal sphincter pressure from 36.5 (SD 18) mm Hg to 48.5 (18) mm Hg (p < 0.0001), irrespective of whether gastro-oesophageal reflux caused oesophageal acidification. Abrupt relaxations of the upper oesophageal sphincter independent of swallowing and lasting up to three seconds occurred during 54% of common cavity episodes. Forty nine per cent of these relaxations occurred within four seconds after the onset of distention. The oesophageal distention caused by gastro-oesophageal reflux is a potent stimulus of transient upper oesophageal sphincter relaxations in children. These relaxations are a more likely explanation for oesophagopharyngeal reflux than defective basal upper oesophageal sphincter tone.